A clinical study on the effects of treating temporomandibular disorder (TMD) by low level laser therapy (LLLT), conservative and combination treatments - Zwiri, Abdalwhab M. A. (2022)
Temporomandibular disorders (TMD) are a common term for a group of musculoskeletal diseases that are associated with pain and/or malfunction in the chewing muscles. They are prevalent among Asians and Malaysians. Treatment modalities involving conservative and LLLT have not been widely investigated, although their potential exists. The aim of this study was to compare the effects of treating TMD by low level laser therapy (LLLT), standard conservative treatment (home based therapy) and the combination treatments. A total of 32 patients aged 18 years and above with TMD were enrolled in three different groups:10 (conservative), 11 (LLLT), and 11 (combined treatments). Purposive sampling method was applied. A proforma for the patient’s history and examination and validated translated questionnaires of Mal-RDC/TMD were used. Pain was measured by Visual Analogue Score (VAS). Patients in LLLT only group and combined treatment group were treated with 5 sessions of low-level laser every other day for a duration of 10 days. Patients in conservative treatment group and combined treatment group received standard conservative TMD treatment (diet and stress counseling, jaw exercises, physical therapy). Blood samples were collected from all groups following universal precautions for venipunctures in comparing hs-CRP, IL-6, IL-8. Descriptive analysis and Repeated measures ANOVA were used for data analysis. Between the three groups (LLLT, conservative, and combined treatment), there was a statistically significant difference in the mean levels of IL-6 (p = 0.037) and IL-8 (p = 0.001). From baseline to post-treatment, the level of anxiety amongst the patients dramatically lowered, although the group did not differ significantly. From baseline to posttreatment, the mean depression index score decreased because of the treatment. There was no significant difference between all treatment groups in terms of jaw disabilites following therapy (p =0.244). Chronic pain intensity score, NSPSE (p = 0.009) score and NSPSI (p < 0.001) significantly decreased from baseline to post treatment, but not significant between the groups. Mean lateral excursion, maximum assisted and unassisted mouth opening all showed significant difference (p < 0.001) before and after the treatment. The mean of VAS significantly (p < 0.001) decreased from baseline to 12 weeks and between three groups (p < 0.010). A significant change was noticed in IL-6 and IL-8. Among the groups with three different treatment modalities, LLLT and combination (LLLT + conservative) treatment approaches were found to be better than the conservative treatment alone.